(3JaSjQ GdbQBf (B( (3bWYI (B)s - (3GdgcGQj , CMeO Hf CMeO Hf CMeO Hf GdMSjf Hf ehSi, TgGH GdOjf,J (B763 (3g` s
(3ChdgG (B:s
(3QHfG dGJRZ bdhHfG ef ShQI Bd YeQGf s
(3BNQgG (B:s
(3ef ShQI GdeGFOI s
(3GdfSNI HgG MhGTs
(3bWYI efgs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs